Contemporary art processes in early childhood education: an artistic research project in teacher training - Font-Company, Enric (2025)
The educational research project Integration and Assessment of Contemporary Art Processes in the Design of Learning Environments was implemented during the 2022-2023 academic year in the Early Childhood Education Teacher Degree program. Conducted under the REDICE 2022 initiative, its primary objective is to design, execute, and evaluate a training proposal based on contemporary art creation processes. The project employed an experimental, mixed-method study through correlational research structured across five distinct phases. The findings indicate significant shifts in students' perceptions and interactions with contemporary art, with a majority recognizing it as a valuable resource for creating impactful learning experiences in Early Childhood Education.